2020
DOI: 10.3390/su12010435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficiency of Sustainable Development Policy Implementation in Selected EU Member States Using DEA. The Ecological Dimension

Abstract: Since the ‘Earth Summit’ in 1992 in Rio de Janeiro, the concept of sustainable development has been widely discussed and implemented globally. This paper proposes a quantitative tool, Data Envelopment Analysis (DEA), that can support decision makers in assessing the efficiency of implementation of the sustainable development policy. The example of such analysis is presented by assessing the efficiency of implementation of the sustainable development policy of twenty two European Union Member States in 2005–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The ecological situation, social issues and economic growth are considered through the prism of the concept of sustainable development. However, studies (Urbaniec 2016), (Lozowicka 2020), (Medved et al 2020), (Huan et al 2019), (Rahma et al 2019) have shown that at the moment there is no clear relationship between the level of environmental safety and progress towards achieving the economic and social goals of sustainable development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological situation, social issues and economic growth are considered through the prism of the concept of sustainable development. However, studies (Urbaniec 2016), (Lozowicka 2020), (Medved et al 2020), (Huan et al 2019), (Rahma et al 2019) have shown that at the moment there is no clear relationship between the level of environmental safety and progress towards achieving the economic and social goals of sustainable development.…”
Section: Resultsmentioning
confidence: 99%
“…The EU countries demonstrate strong positive shifts in ecological issues (even with a lag in the socioeconomic sphere) due to reduction of greenhouse gas emissions and primary energy consumption (Urbaniec 2016). In Europe, the high efficiency of the implementation of sustainable development policies is achieved by environmental protection dictated by ecological culture and economic considerations (Lozowicka 2020). In the cities of South Korea, China, Germany, and Sweden the sustainable urban development is primarily associated with technical solutions in the field of environment and, to a lesser extent, with the solution of social issues.…”
Section: Introductionmentioning
confidence: 99%
“…In the energy sector, Chai, Fan, and Han [43] use the DEA with some novelties to determine the efficiency in this sector, justifying its use in that you have great advantages in avoiding subjective factors, simplifying algorithms, and reducing errors; it gradually developed into one of the most commonly used tools for evaluation efficiency in many fields. This same DEA model has also been used in the environmental sector, by Łozowicka [44] to measure the efficiency of European community countries. In the water industry, Sun, Yang, Zhang, and Chen [45] evaluated the efficiency of the use of this product in the municipalities of China, using the traditional DEA model, but modifying the indices used.…”
Section: Methodsmentioning
confidence: 99%
“…This second stage, EDA with these proposed indicators, is expected to better characterize the efficiency and sustainability of CDW management than using the previously introduced parameters. Previous works [34] have successfully used DEA for assessing the ecological dimension of sustainability in the EU. Some of the most relevant contributions of this set of candidate indicators are: (i) characterizing the building stock through year construction, average age, and type of construction; (ii) using the dwelling occupancy ratio as proxy for the habitational needs; (iii) use of Gross Value Added (GVA) rather than GDP, as it accounts more directly for the value provided by sector activity (without taxes and subsidies); and (iv) providing ratios for CDW management Key Performance Indicators (KPIs).…”
Section: New Indicators For Assessing the Efficiency And Sustainabilimentioning
confidence: 99%
“…The use of a Directional Distance Function (DDF) allows for the simultaneous increase in desirable outputs and reduction of undesirable outputs [39]; however, for reasons of simplicity, DDF and other approaches, such as DEA-Malmquist and Slacks-Based Measure (SBM) DEA, have been kept for future work. Malmquist and SBM have been used in [34] with four input and four output variables not directly related.…”
Section: Data Envelopment Analysis (Dea) For Assessing the Efficiencymentioning
confidence: 99%